Effectiveness of DILA Learning Model Application on Applied Physics Course in The Department of Mining Engineering - Fadhilah, F.; Effendi, Z. M.; Ridwan, R.; Alias, M. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2019)
There is the fact that the students' learning outcome in Applied Physics course related to the application of the mining industry is unsatisfactory. Based on the results of the final score, the rate of successful students was only around 40%. Moreover, students' understanding application is also not by the desired competencies. In this research, a learning model was developed from the Contextual Teaching and Learning Model (CTL), i.e., DILA model which consists of four syntaxes (Display, Inquiry, Learning Community, and Authentic Assessment). The effectiveness of the DILA learning model was investigated to improve students’ learning outcomes in the Applied Physics course. This research employed the quasi-experimental design where the experimental class was treated by DILA model based on Contextual Teaching and Learning; whereas control class was not treated by the model. Data were obtained from the results of the pre-test and post-test scores; then it was analyzed by a parametric with an independent t-test, related t-test, and the effect size. The results indicate that there was a significant increase in students’ learning outcomes in the experimental class compared to the control class. In conclusion, DILA model can improve students’ learning outcomes in the Applied Physics course effectively.Hasil belajar Fisika Terapan yang diperoleh mahasiswa yang terlihat dari nilai akhir semester dan penerapan pada industri pertambangan pada umumnya tidak memuaskan. Tingkat kelulusan mahasiswa hanya sekitar 40%. Sehingga pemahaman mahasiswa dalam penerapannya juga tidak sesuai dengan kompetensi yang diinginkan. Model DILA merupakan salah satu model pembelajaran yang dikembangkan dari Model Contextual Teaching and Learning (CTL). Model DILA terdiri atas empat sintaks yaitu: Display, Inquiry, Learning Community, dan Authenthic Assessment. Penelitian ini ditujukan untuk mengukur efektifitas Model Pembelajaran DILA guna meningkatkan hasil belajar mahasiswa pada matakuliah Fisika Terapan. Penelitian ini merupakan quasi eksperiment dimana kelas eksperimen diberikan pembelajaran dengan Model DILA berbasis Contextual Teaching and Learning. Data diperoleh dari hasil pre-test dan post-test dan diolah secara parametric dengan t test sample independent dan t test related serta effect sizenya. Hasil penelitian ini menunjukkan bahwa model pembelajaran DILA yang diterapkan pada matakuliah Fisika Terapan di Jurusan Teknik Pertambangan adalah efektif. Ini berarti model Pembelajaran DILA dapat meningkatkan hasil belajar mahasiswa pada matakuliah Fisika Terapan.